Revisiting 'curriculum crisis' dialogue: in search of an antidote - Armend Tahirsylaj (Taylor & Francis Group, 2019)
This article builds upon the international dialogue around 'curriculum crisis' initiated by Michael Young in Journal of Curriculum Studies (JCS) in 2013 and followed up in JCS in 2015. It seeks to expand the dialogue in three avenues. First, when considered from a sociological perspective, Young is correct to declare 'curriculum crisis'; however, his position is limited only to the conflict theory. Second, from educational perspectives, the curriculum crisis as such is self-inflicted and it has been more of a battle among different curriculum ideologies in the Anglo-Saxon world and resistance to Bildung-centred Didaktik tradition in the Western world more broadly. Third, it points to the fourth industrial revolution as an inevitable phase. It concludes that 'curriculum crisis' is only partially about bringing knowledge back in, and the article suggests 'the prepared mind' as a metaphor to bridge knowledge and learning outcome perspectives. Specialized knowledge in curricula will become even more relevant in the innovation age, and a prepared mind adaptable to the changing world and open to continued learning can assist individuals navigate life and career creatively, meaningfully and constructively.